Student-Athlete Male-Perpetrated Sexual Assault Against Men: Racial Disparities in Perceptions of Culpability and Punitiveness - Powers, Ráchael A. (American journal of criminal justice, 2023)
Racial disparities in perceptions of sexual assault incidents have largely focused on male-perpetrated violence against women. However, in some contexts such as college sports, sexual victimization of men may disproportionately impact racial minorities. Therefore, it is necessary to examine sexual assault in these contexts. Using a 2 × 2 factorial survey experimental design with vignettes pertaining to a collegiate athlete sexual assault scenario involving two male student-athletes, we examined perceptions of (1) racial differences in offender motivation, (2) racial differences in victim culpability, and (3) racial differences in preferred sanctions. Compared to the White-White scenario, participants in the Black-Black scenario perceived the perpetrator to be less motivated by power and control or mental health/bad upbringing. Black victims of White-perpetrated sexual assault were perceived as more able to offer physical resistance and therefore partially culpable for the incident. Finally, participants were more punitive for the scenarios involving Black offenders, especially when the victim was White. Participants were harsher in their preferences for both university sanctions and criminal justice sanctions, with the Black-White scenario producing a greater likelihood of recommending expulsion and incarceration. We discuss the implications of our findings for understanding racial disparities in sexual assault generally, as well as for college student-athlete contexts.